Performance of Agricultural Extension Services (BPP) in Enhancing Rice Production in North Sumatra, Indonesia - Gurning, Riris Nadia Syafrilia; Puarada, Sakral Hasby; Lubis, Wildani; Nurhajijah, Nurhajijah (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
Indonesia has experienced an increase in national population, the Government is targeting rice production of 54.50 million tons in 2023. North Sumatra Province has the largest rice production on the island of Sumatra, 2,088,584 tons. The effectiveness of the Agricultural Extension Service (BPP) in Percut Sei Tuan is of concern to researchers. This research method uses a differential semantic measurement scale or attitude scale to analyze performance data. The number of samples determined in the research was 10 farmers per village so that the number of samples from all villages was 30 rice farmers with 5-point rating scale and the choices "Very Good" to "Very Poor" with the interval scale formula {a(m-n)}/b and the number of question attributes is 12 points, and the class interval is 9.6. The results performance is in the "Very Good" performance category with an average score of 4.24. However, based on their respective scores of 3.03, there is a low score of 2.53 in the category of agricultural extension officers who do not assist farmers in obtaining agricultural financing, nor do they help market their agricultural products. Extension officers have carried out but are still not optimal with answers from one research category.